2016
DOI: 10.1177/1099800416683801
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acupressure on Meridian Energy as well as Nausea and Vomiting in Lung Cancer Patients Receiving Chemotherapy

Abstract: Nausea and vomiting are the most common side effects of antineoplastic chemotherapy. However, only a small number of studies have been conducted in Taiwan to determine the efficacy of acupressure in treating these side effects in cancer patients receiving chemotherapy. In this quasi-experimental study, we aimed to explore the effects of acupressure on meridian energy as well as nausea and vomiting in 70 lung cancer patients receiving chemotherapy. Patients were assigned to the experimental or control group bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
6
1
2
Order By: Relevance
“…They added that, the development of acupressure as a nursing intervention, dependent on a theoretical concept, evidence based studies, and practical nursing experience represents a very important step for the future of the nursing care of cancer patients undergoing chemotherapy. [40,41] In contrast with results of the current study, Wulffa et al (2009) stated that, no significant benefit was experienced with children who were subjected to acupressure in the control of CINV. [42] Also contradictory to the present study findings a single blinded randomized trial was conducted by Genc et al (2013) on the efficiency of acupressure in the prevention of CINV among 120 patients with breast, gynecological, and lung cancers.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…They added that, the development of acupressure as a nursing intervention, dependent on a theoretical concept, evidence based studies, and practical nursing experience represents a very important step for the future of the nursing care of cancer patients undergoing chemotherapy. [40,41] In contrast with results of the current study, Wulffa et al (2009) stated that, no significant benefit was experienced with children who were subjected to acupressure in the control of CINV. [42] Also contradictory to the present study findings a single blinded randomized trial was conducted by Genc et al (2013) on the efficiency of acupressure in the prevention of CINV among 120 patients with breast, gynecological, and lung cancers.…”
Section: Discussioncontrasting
confidence: 89%
“…[39] Shen and Yang (2017) concluded that, acupressure significantly increased the mean meridian energy and effectively decreased the severity of nausea and vomiting in lung cancer patients undergoing chemotherapy and recommend that, clinical nurses should provide acupressure as an intervention to relieve nausea and vomiting in patients receiving chemotherapy. [40] Byju et al (2018) evaluated the effectiveness of acupressure on the experience of nausea and vomiting among patients receiving chemotherapy and concluded that, acupressure is an effective method for reducing nausea and vomiting among patients receiving chemotherapy. [41] Many studies tried to explain how acupressure on certain points improve CINV and reported that acupressure application on the affected meridians on the body surface could increase the flow of energy, boost meridian energy, improve blood circulation and promote the recovery of gastrointestinal function and hence effectively reduce CINV.…”
Section: Discussionmentioning
confidence: 99%
“…Descreve-se, em relação aos tipos de acupuntura realizados no estudo, que quatro artigos utilizaram o método da eletroacupuntura para tratar náuseas e vômitos, 16,20 dois estudos investigaram a resposta da acupuntura auricular nos quadros de náuseas induzidos pela quimioterapia, um deles, com crianças, 14,18 três estudos relataram as respostas da acupressão em pontos de acupuntura no tratamento e prevenção de náuseas e êmese. 17, Aponta-se que três estudos analisaram o efeito da acupuntura para diminuir diversos efeitos adversos, incluindo náusea, [9][10][11] um estudo abordou o efeito das práticas integrativas, incluindo acupuntura, em crianças na fase de tratamento, 15 quatro estudos investigaram os efeitos do ponto de acupuntura PC6 8,12, e, por fim, um estudo analisou a ação da acupuntura clássica relacionada ao antiemético no tratamento e prevenção de náuseas e vômitos. 19 Registra-se que o efeito da acupuntura no controle de náuseas e vômitos induzidos pela quimioterapia foi benéfico e eficaz em 13 estudos,…”
Section: Objetivo Métodounclassified
“…One of the acupressure points to reduce chemotherapy-induced nausea and vomiting is the Nei Guan point. A study conducted by Shen & Yang (2016) state that Nei Guan acupressure therapy can significantly increase energy on the meridian line by reducing severe vomiting nausea in cancer patients receiving chemotherapy. This acupressure point is easier to use in pediatric patients than other positions because the location of the pressure point is accessible, easy to learn, non-invasive and recommended for the recovery of the digestive tract (Miao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%